2010
DOI: 10.1111/j.1399-0012.2010.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with positive attitudes toward organ donation in Arab Americans

Abstract: Arab Americans represent a growing population about which little is known in regard to organ donation and transplantation. This population is not specifically captured within national and local transplantation databases, and little empiric work has assessed attitudes and barriers toward organ donation and transplantation within this community. Our work represents the first to use a representative population-based sample to explore the modifiable and non-modifiable characteristics of those who believe cadaveric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 64 publications
0
27
0
1
Order By: Relevance
“…Similarly, in the USA, greater acculturation of immigrants is associated with greater odds of believing organ donation to be justified. 17 This tension between migrant generations, referred to as an intergenerational acculturation gap, [23][24][25] has been linked to family and social conflict and adjustment. [26][27][28][29] Thus, it is not surprising that our study found that many were concerned about negative appraisal by their family and community, and anticipated family resistance and conflict if they are registered as an organ donor.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the USA, greater acculturation of immigrants is associated with greater odds of believing organ donation to be justified. 17 This tension between migrant generations, referred to as an intergenerational acculturation gap, [23][24][25] has been linked to family and social conflict and adjustment. [26][27][28][29] Thus, it is not surprising that our study found that many were concerned about negative appraisal by their family and community, and anticipated family resistance and conflict if they are registered as an organ donor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our outcome measure assesses whether decreased organ donation is ''justifiable.'' We chose this wording to build upon our previous work with the Detroit Arab American Study (45). Yet, phrasing that connotes an ethical judgment regarding organ donation may not accurately measure one's willingness to donate their own or a relative's organs or other organ donation behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…African Americans (35%), Arab Americans (25Y30%), and South Asian Americans (20%Y25%) are the dominant racial/ ethnic groups within this community (40,44). Our previous research examined a population-based representative survey of Detroit area Arab Americans and revealed that Muslim Arabs had decreased odds of believing deceased organ donation to be justified (45). The exploratory research we present herein builds upon that work by exploring relationships between religiosity and attitude toward deceased organ donation among a diverse group of American Muslims.…”
mentioning
confidence: 98%
“…In a study conducted in late 2003 among Greater Detroit Arab Americans found Christian Arab Americans more likely than Muslim Arab Americans to believe organ donation after death being justifiable. Higher educational attainment and income, as well as greater acculturation into American society, were associated with greater odds of believing organ donation to be justified [5]. Regarding people's awareness about organ donation, a national study was conducted in China which showed that nearly 94% of the people in China were aware of organ donation.…”
Section: Introductionmentioning
confidence: 99%